Slobodan pristup informacijama i zaštita intelektualnog vlasništva - Horvat, Aleksandra knjižničarka (2009)
Provision of free access to information is the basic task of the library profession.. Numerous international documents on libraries emphasize this task and the need for the libraries - as important social institutions that stimulate the development of democracy and social inclusion - to provide different types of information on various media to all categories of library users. Legal regulations on copyright, the right od distributors and producers of information can diminish or even prevent libraries in their task of ensuring free access to information. Therefore every organized and democratic society aims to strike a balance between the public interest and the interest of copyright holders. In the cintemporary society the scope and length of copyriright protection have been widened. This could seriously damage the role of libraries as public institutions facilitating free access to information.
Projekt MZOS
HRV